Beyond traditional proxies: the contribution of leisure to cognitive reserve and dementia - Ottaviani, Silvia; Tagliafico, Luca; Peruzzo, Stefania; Ponzano, Marta; Signori, Alessio; Nencioni, Alessio; Monacelli, Fiammetta (Frontiers in Aging Neuroscience, 2025)
IntroductionCognitive reserve (CR) is a multidimensional construct based on lifelong engagement in cognitively stimulating domains, including education, occupation and leisure activities, that plays a crucial role in mitigating the presentation of dementia. To date, the contribution of each CR subdomain in the development of dementia is under-investigated. This study is aimed at assessing the association of CR subdomains with cognitive status, accounting for sex and age in an old-age population.Methods317 older adults were recruited with a diagnosis of subjective cognitive impairment, mild cognitive impairment, and dementia due to Alzheimer’s disease or mixed-type dementia. Cognitive Reserve Index questionnaire (CRIq) was used to assess CR. Patients were stratified based on sex and dementia staging (CDR). Significant variables from univariate analysis entered a multivariate ordinal regression model, using CDR as the dependent variable.ResultsThe results showed that the leisure activities subdomain was the main determinant of cognitive status (OR 0.90, 95%CI 0.82–1.00, p = 0.003); CR and sex did not show any interaction.DiscussionUnlike education and occupation, leisure activities may be considered a lifelong, dynamic contributor to CR. These findings highlight the importance of refining CR assessment, with particular attention to leisure activities as a potentially modifiable target for dementia prevention.